Decreased respiratory symptoms in cannabis users who vaporize - Barnwell Sara; Earleywine Mitch (BMC, 2007)
Abstract Cannabis smoking can create respiratory problems. Vaporizers heat cannabis to release active cannabinoids, but remain cool enough to avoid the smoke and toxins associated with combustion. Vaporized cannabis should create fewer respiratory symptoms than smoked cannabis. We examined self-reported respiratory symptoms in participants who ranged in cigarette and cannabis use. Data from a large Internet sample revealed that the use of a vaporizer predicted fewer respiratory symptoms even when age, sex, cigarette smoking, and amount of cannabis used were taken into account. Age, sex, cigarettes, and amount of cannabis also had significant effects. The number of cigarettes smoked and amount of cannabis used interacted to create worse respiratory problems. A significant interaction revealed that the impact of a vaporizer was larger as the amount of cannabis used increased. These data suggest that the safety of cannabis can increase with the use of a vaporizer. Regular users of joints, blunts, pipes, and water pipes might decrease respiratory symptoms by switching to a vaporizer